Implementation of Sorogan Method Based Java Pegon in Learning of Kutub At-Turats - M. Syahrul Anwar; Riski Janu Saputra; Umi Machmudah (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2022)
Pondok Modern Al-Rifa'ie 2 Malang has implemented the java-based sorogan method pegon in the learning of the book at-turast, because the characteristic of the islamic boarding school is to teach the holy book of the Qur'an and the book of turast, both modern and salaf huts. This study aims to: (a) find out the application of the Javanese pegon touch-based sorogan method in learning the book of at-turat for students at the modern Islamic boarding school Al-Rifaie 2. (b) knowing the advantages and disadvantages of applying the Javanese pegon touch-based sorogan method in learning the at-turat book for students in the modern islamic boarding school Al-Rifaie 2. Researchers use qualitative type research with a case study approach at the Al-Rifa’ie 2 Islamic Modern Boarding School. Data collection is carried out through observation, interviews and documentation, while data analysis uses the techniques of Miles Huberman and Saldana, namely: data collection, data condensation, presentation of data, and drawing conclusions. The results of this study the sorogan method is one of the methods used in balancing the application and learning of the at-turast poles in the Al-Rifa'ie Modern Cottage and the implication of this research is that teachers can develop and preserve the sorogan method in at-turast polar learning.